2015
DOI: 10.3389/fpls.2015.00553
|View full text |Cite
|
Sign up to set email alerts
|

EXTENSIN18 is required for full male fertility as well as normal vegetative growth in Arabidopsis

Abstract: EXTENSINS (EXTs) are a 65-member subfamily of hydroxyproline-rich glycoproteins (HRGPs) of which 20 putatively form crosslinking networks in the cell wall. These 20 classical EXTs are involved at the start of new wall assembly as evidenced by a requirement for EXT3 during cytokinesis, and the ability of some EXTs to polymerize in vitro into dendritic patterns. EXT3 was previously shown to form pulcherosine (three Tyrosines) cross-links. Little direct data exists on the other 19 classical EXTs. Here, we describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 61 publications
(74 reference statements)
1
24
0
Order By: Relevance
“…For flowering time experiments, plants were grown in inductive photoperiods/LD (LD1, 16 h light/8 h dark; LD2, 12 h light/12 h dark) and non‐inductive photoperiods/SD (SD1, 10 h light/14 h dark; SD2, 8 h light/16 h dark). Flowering time analysis was performed as described previously (Choudhary et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…For flowering time experiments, plants were grown in inductive photoperiods/LD (LD1, 16 h light/8 h dark; LD2, 12 h light/12 h dark) and non‐inductive photoperiods/SD (SD1, 10 h light/14 h dark; SD2, 8 h light/16 h dark). Flowering time analysis was performed as described previously (Choudhary et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Previous studies have demonstrated that extensins are required for normal vegetative growth, male fertility and disease tolerance. Mutation of extensins genes leads to fewer leaves and reduced plant size and fertility in Arabidopsis (Cannon et al ., ; Choudhary et al ., ; Saha et al ., ). Short and irregular root hair lengths are also observed in the insert mutations of AtEXT6 , 7 , 10 , 11 , 12 and 13 (Velasquez et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Extensin18 (EXT18), a Hyp-rich glycoprotein, appears to direct pollen tube structure and growth (Choudhary et al, 2015). EXT18-null mutants are less fertile, which may result in part from reduced pollen tube growth but also from an increase in pollen tube bursting (Table I).…”
Section: Cell Wallmentioning
confidence: 99%